"Mój kraj to szczyt gotyckich wież". Romantyczne portrety katedr w epistolografii Zygmunta Krasińskiego - Łuczkowski, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
Sights of gothic cathedrals in Zygmunt Krasiński’s letters are proves of his great and deep fascination of medieval times. Following the examples of Goethe, Chateaubriand, and Friedrich he defines beauty of gothics churches. Such conact with a monumental architecture seems to be a pretext to estetic and philosophical reflections. Not only did he touch a matter of light in order to show the organic style of architecture, but also emphazised the importance of this case in creating a special style. View of the church remains have got also some kind of a metaforic meaning fог the times that passed by and a symbol of previous generations. It makes us think about the significance of our life.